Gaming gray zone tactics design considerations for a structured strategic game - Wasser, Becca (RAND, 2019)
To explore how Russia could use gray zone tactics and to what effect, the authors of this report developed a strategic-level structured card game examining a gray zone competition between Russia and the West in the Balkans. In these games, the Russian player seeks to expand its influence and undermine NATO unity while competing against a European team and a U.S. team seeking to defend their allies from Russia's gray zone activities without provoking an outright war. This report details the authors' development of this game, including key design decisions, elements of the game, how the game is played, and the undergirding research approach. The authors conclude with recommendations for future applications of the game design
"RAND Arroyo Center."
"Prepared for the United States Army."
"This research was conducted within RAND Arroyo Center's Strategy, Doctrine, and Resources Program"--Preface (page iii)
Keywords: National security / Balkan Peninsula; War games; Balkan Peninsula / Defenses; Balkan Peninsula / Foreign relations / Russia (Federation); Russia (Federation) / Foreign relations / Balkan Peninsula; Europe / Foreign relations / Russia (Federation); Russia (Federation) / Foreign relations / Europe; United States / Foreign relations / Russia (Federation); Russia (Federation) / Foreign relations / United States